Spousal Caregiving for Partners With Dementia: A Deductive Literature Review Testing Calasanti's Gendered View of Care Work. (July 2016) - Hong, Sung-chull; Coogle, Constance L.
Spousal caregiving allows stressed couples to continue living in the community rather than seeking institutional solutions. Dr. Toni Calasanti has postulated that there are gender differences in the care work styles and coping strategies used by spousal caregivers dealing with dementia. While caregiving husbands tend to adopt task-oriented (masculine) approaches, caregiving wives are more likely to take an emotionally focused (feminine) orientation. These differences result in the need for varied interventions. Male caregivers tend toward a managerial approach, whereas female caregivers generally adopt a relational approach. This distinction was examined in the course of a literature review through the deductive process. It was determined that the core thesis of such a gender-based view of care work as a tiered entity threaded with masculinity/femininity remains quite plausible in contrast to models based on self-perceived gender identity of caregivers that require more exploration. Recommendations for future investigations are offered as new questions arise.